PROGRAM KEMITRAAN PENGEMBANGAN JAGUNG MANIS DENGAN SISTEM TANAM LEGOWO DI KABUPATEN TAKALAR - Subaedah, St.; Saida, Saida (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2020)
Paddingin Village, Sanrobone Subdistrict, Takalar Regency is one of the areas that is the center ofcorn development and is also one of the target areas of the Indonesian Muslim University. Duringthis time, farmers planted sweet corn with a conventional system with a spacing of 70 cm x 25 cm,so that the production obtained was not optimal. Besides that, the time of harvest is not givenmuch attention, while the quality of sweet corn (sugar content) is determined by the exact time ofharvest. This activity aims to provide knowledge and skills for the community in PaddinginVillage especially the Sweet Corn Farmer Group in sweet corn cultivation which includes sweetcorn planting techniques with the Legowo system and the determination of the right harvest time,so that the growth and production and quality of sweet corn produced can be maximized . Themethods used in the implementation of the Science and Technology Program for Communities arecounseling, training, production assistance, and demonstration plots. The results of this partnershipprogram are an increase in farmers' understanding and skills in cultivating sweet corn plants withthe Legowo 2: 1 system, and an increase in sweet corn production obtained by farmers by 35%.